Application of a time-varying covariate model to the analysis of CA 19-9 as serum biomarker in patients with advanced pancreatic cancer - Böck, Stefan; Haas, Michael; Laubender, Rüdiger P.; Kullmann, Frank; Klose, Christina; Bruns, Christiane J.; Wilkowski, Ralf; Stieber, Petra; Holdenrieder, Stefan; Buchner, Hannes; Mansmann, Ulrich; Heinemann, Volker (Clinical cancer research, 2010)
Purpose: The clinical relevance of CA 19-9 as surrogate biomarker in advanced pancreatic cancer is a matter of debate.Experimental Design: This retrospective multicenter study included patients with histologically confirmed advanced pancreatic cancer treated with first-line therapy. Analysis of CA 19-9 was done using the Elecsys assay (Roche Diagnostics). For an analysis of CA 19-9 kinetics, at least three measurements during first-line chemotherapy had to be available. The effect of pretreatment CA 19-9 levels on time-to-progression (TTP) and overall survival (OS) was modeled by Cox proportional hazards regression. The effect of CA 19-9 kinetics was also modeled by Cox proportional hazards regression where CA 19-9 was treated as a time-varying covariate.Results: One hundred and fifteen patients from five German centers were included; 73% of them were treated within prospective clinical trials. Median TTP was 4.4 months and median OS was 9.4 months; univariate analysis indicated that pretreatment CA 19-9 [as continuous variable, log (CA 19-9)] was significantly associated with TTP [hazard ratio (HR), 1.24; P < 0.001] and OS (HR, 1.16; P = 0.002). These associations remained significant within multivariate analysis. For CA 19-9 kinetics during chemotherapy, data from 69 patients (TTP) and 84 patients (OS) were available, respectively; log (CA 19-9) kinetics after start of treatment were found to be a significant predictor for TTP in univariate (HR, 1.48; P < 0.001) and multivariate (HR, 1.45; P < 0.001) analyses, and also for OS (univariate: HR, 1.34; P < 0.001; multivariate: HR, 1.38; P < 0.001).Conclusion: Pretreatment CA 19-9 and CA 19-9 kinetics may serve as a useful serum biomarker in advanced pancreatic cancer. Clin Cancer Res; 16(3); 986-94
Gesehen am 26.01.2023